Investigation of Drainage and Waste Water Quality for the Improvement of Technological Treatment Solutions - DOMASHENKO, Yulia; VASILYEV, Sergey; VASILYEV, Dmitry (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The purpose of this work is to study the qualitative indicators of drainage and waste water from irrigated areas in order to justify the treatment technology. The research was carried out within the Bagayevskaya irrigation system located in the Rostov Region, the Russian Federation. The location of the well is confined to the second terrace above the floodplain of the Western Manych River. The chemical composition of drainage water allows us to refer this water category to the sulfate class, the sodium group of a partially mixed cationic composition. The type of drainage water is sulfate sodium and sulfate calcium. In drainage runoff, there are no chlorine-magnesium waters, even in the autumn period. The content of biogenic elements during the observation period in the investigated wells was within the following limits: phosphates – from 0.04 to 0.75 mg/dm3, ammonium ions – from 0.07 to 1.35 mg/dm3, and nitrates – from 0.05 to 0.43 mg/dm3. An improved treatment method of drainage and waste water for crop irrigation is proposed. It includes the removal of mechanical impurities and petroleum products (in the first stage) on coalescent modules installed directly on the discharge or drainage channel in the form of a framework module and the release of heavy metal ions, organic substances and excess salts (in the second stage) in the sorption block, which includes three sorption layers – S-VERAD, zeolite and quartz in an equal ratio, placed in a grid of a filter cassette of the cassette-holding device.